99.4k views
0 votes
How do I solve for V1 in this equation ​

How do I solve for V1 in this equation ​-example-1
User Geny
by
4.8k points

1 Answer

4 votes

Answer:


V_(1) = (P_(2)V_(2)T_(1))/(P_(1)T_(2))

Step-by-step explanation:


(P_(1) V_(1))/(T_(1)) = (P_(2)V_(2))/(T_(2))

First of all cross multiply

That's


P_(1)V_(1)T_(2) = P_(2)V_(2)T_(1)

Next divide both sides by
P_(1)T_(2) in order to isolate
V_(1)

We have


(P_(1)V_(1)T_(2))/(P_(1)T_(2)) = (P_(2)V_(2)T_(1))/(P_(1)T_(2))

We have the final answer as


V_(1) = (P_(2)V_(2)T_(1))/(P_(1)T_(2))

Hope this helps you

User Basin
by
4.4k points